(untitled) (International Journal of Engineering and Computer Science, 2017)
In sensing and pervasive computing ad-hoc low-power wireless networks are an exciting research. Prior security work has first focused on denial of communication at the routing or levels of media access control. This paper examine resource depletion attacks at routing protocol layer, which disable networks by quickly draining node’s battery power. These “Vampire” attacks are not specific to any particular protocol, but rather depend on the properties of many well known classes of routing protocols. We find that all examined protocols are affected to Vampire attacks ,which are destructing, hard to detect, and are easy to carry out using as few as one malicious insider sending only protocol compliant messages. In case of worst case, a single Vampire can increase network-wide energy usage by a factor of O(N), where N in the number of nodes of network. The methods we discuss to mitigate these types of attacks which includes a new proof-of- concept protocol that bounds the damage caused by Vampires during the packet forwarding phase.